Utilization of the impact index to interpret the relative influence of edaphoclimatic factors on the production of tropical pasture seeds - Febles, Gustavo; Torres, Verena; Ba?os, R.; Ruiz, Tom?s E.; Y??ez, S.; Echeverr?a, Jahel (Cuban Journal of Agricultural Science, 2011)
An experiment was designed to know the impact index. The application of this technique admits combinations of species within each edaphoclimatic region. The impact index depends on the indicators of higher preponderance that appear in the analysis of the principal components and corresponding with them. The result generates values that, according to their number hierarchy, express the highest or the lowest effect of each indicator per region. The data came from farms for seed production, located in specific regions of the Cienfuegos, Villa Clara, Sancti Sp?ritus, Camag?ey, Granma and Guant?namo provinces. The species were: Panicum maximum, Andropogon gayanus, Brachiaria decumbens, Brachiaria brizantha, Chloris gayana and Cenchrus ciliaris. The results showed the preponderance of the factors: total rainfall and rainfall in the rainy season; maximum, medium, and minimum temperatures; effective depth; amount of rocks; and light hours. The indicators of the first component had the highest impact index in Guant?namo, followed by Granma and Camag?ey. They showed lower value in Cienfuegos, with more negative figures. In the first impact index, 45.4 % of the indicators of higher preponderance were found in the analysis of the principal components. Andropogon gayanus reached the highest values in Guant?namo, Granma and Camag?ey, being followed by Panicum maximum, Cenchrus ciliaris and Brachiaria brizantha, respectively. This result showed a closer relationship between the species in the regions under study. It is concluded that the mathematical methods used were potentiated by the determination of the impact index. The importance of the methodology is discussed, as well as the study of the localities and the possible effect of the impact index on the interaction genotype-environment. Key words: impact index, multivariate analysis, production of seeds, grasses.